3x+27=10x-33

Simple and best practice solution for 3x+27=10x-33 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+27=10x-33 equation:


Simplifying
3x + 27 = 10x + -33

Reorder the terms:
27 + 3x = 10x + -33

Reorder the terms:
27 + 3x = -33 + 10x

Solving
27 + 3x = -33 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
27 + 3x + -10x = -33 + 10x + -10x

Combine like terms: 3x + -10x = -7x
27 + -7x = -33 + 10x + -10x

Combine like terms: 10x + -10x = 0
27 + -7x = -33 + 0
27 + -7x = -33

Add '-27' to each side of the equation.
27 + -27 + -7x = -33 + -27

Combine like terms: 27 + -27 = 0
0 + -7x = -33 + -27
-7x = -33 + -27

Combine like terms: -33 + -27 = -60
-7x = -60

Divide each side by '-7'.
x = 8.571428571

Simplifying
x = 8.571428571

See similar equations:

| -40=33x+15 | | 3=-x+1 | | 6(2x+1)-3(5x+2)=0 | | 8=8n-22-7n | | -x+3= | | y=-0.02x+x+6 | | 7=3(x-7)+10 | | 8x=16(x-36) | | x=-5+4 | | 3x+15=6x+7 | | 3(2-a)=8-a | | 3x-8=5(2x-3) | | 147-4x=23x+21 | | 5x=(6x-3) | | 5(2x-3)+6=43-3x | | 8+12x=15x-19 | | 2c+5=3c+7 | | 67-5x=9x+7 | | 3a-11=4 | | 60-x=2(x-36) | | 2x+6=-3 | | 104-x=2(x-29) | | 20x-9x-20=0 | | 3x+139=12x-14 | | x-9x-20=0 | | 4x-2=11x-43 | | 49-6x=12x+15 | | 5m(2m-7)=-5 | | -8x-y=-8 | | x^3-8x^2+15x+12=0 | | 2x^2-11x-24=0 | | 2(x+3)-3=8-2x |

Equations solver categories